OVERVIEW OF STRESS LEVELS IN THIRD AND FOURTH-YEAR FEMALE STUDENTS - Putri, Pramita Ariawati; Nurmutia, Paramita Adi; Parinduri, Fitri Khoiriyah; Firdaus, Tiara Afini; Fatmawati, Siti; Luthfiar, Syafna Laila; Nadhifah, Salsabila; Maulida, Tia Amel (HEARTY, 2024)
Physical demands, environmental and social situations that cannot be controlled can cause stress, stress the third and fourth years, can be caused by the many responsibilities that must be completed. Third and fourth year students could have vary stress levels, the objective of this study was to determine stress level on students in semester 6 and 8 of the FIKES, UIKA Bogor. Sample size was 33 female college students in 6th and 8th semester, obtained with consecutive sampling. The research method used descriptive analytic study design. Data on stress level were obtained by filling out stress part in DASS-21 questionnaire through google form in June-July 2023, and univariate analysis was used for the data. The results showed that more than half subject (55%) had normal stress level, meanwhile mild and moderate stress level were 15% each. Severe (9%) and extremely severe (6%) stress level were also founded in this research. Most of the stress levels in final years students at FIKES UIKA Bogor were normal, but treatment is needed for subjects who have severe and extremely severe stress. Screening for stress from faculty can be held to prevent severe stress and college students need to know about stress management. Future research can involve more samples regarding stress factors and stress education intervention in semesters 6th and 8th girl college student.